(untitled) (Journal of Pakistan Orthopaedic Association, 2024)
Objective: The study aimed to identify patient satisfaction and barriers to successful completion of video telemedicine follow-up in orthopaedic postoperative care at Tertiary Care Hospital. Methodology: Patients of any age who received telemedicine follow-up postoperatively at the Department of Orthopedic & Spine Center, Ghurki Trust Teaching Hospital, Lahore, from the period (1st September to 30th September 2022). The opportunity to respond over the phone, get a link through email, or deny participation was provided to caretakers when they were reached by phone. We determined the degree of satisfaction using the Telemedicine Satisfaction Questionnaire (TSQ) created by Yip et al. All the data were entered and analyzed using Excel and SPSS software Version 28. Results: Among 98 patients, 20 followed up through teleclinic, 15 came in OPD for follow-up, and 63 failed visits were observed. In our study, more than half of cases, 13(85%), were male, and fewer than 7(35%). The average age of the patients was (M=33.30, SD=13.98), ranging from 6 to 70 years. 65% of cases belonged to rural areas, and 35% were from urban areas. The primary language of half of the patients was Urdu (50%), then (40%) had the primary language of Punjabi, 1 case only understood the language of Pushto, and 1 case with Siraki because of their primary language. The results concluded that 17(85%) patients were satisfied after telemedicine visits, while only 2(15%) were dissatisfied. The results reveal that only primary language was the significant predictor affecting Patient Satisfaction as p<.05. Fifteen cases did not send their discharge cards to WhatsApp because of some internet issues. Nine patients did not respond to our call. So, these were the hurdles observed in our study for successful telemedicine follow-up completion. Conclusion: Our study provides further evidence that telemedicine could have a favorable impact. Due to its ease, carers supported this service. In this study, several characteristics were shown to be associated with patient satisfaction and telehealth. Understanding these variables might aid implementers in matching treatments as solutions to particular issues.